Family-centered maternity care mobile application to increase the readiness of pregnant women in facing a high-risk childbirth - Mayasari, Senditya Indah; Jayanti, Nicky Danur (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2020)
Background: Pregnant women with high risk need education and information along with the pregnancy. Information support helps them to feel ready and confident to go through the delivery. Sources of Information that can be accessed during pregnancy include websites regarding pregnancy, smartphone applications, magazines, and books. One of the efforts to increase pregnant women's readiness to face childbirth is by providing Family Centered Maternity Care (FCMC) education through Mobile Applications. Objective: This study aims to develop and test the FCMC mobile application's effectiveness to help pregnant women's readiness with a high risk of childbirth. Method: This study employed Research & Development consisting of 4 stages, namely Literature Study, Development Stage, Validity Expert, and Trial. Results: FCMC Mobile application has been created with nine features, starting from pregnancy features to delivery preparation. The trial results showed that the application effectively increased pregnant women's readiness to face childbirth (p <0.001). Conclusion: The FCMC is a form of midwifery technology that makes it easier for health workers to educate pregnant mothers, especially mothers with high-risk pregnancies. By applying the apps, pregnant women can prepare for the process before childbirth in physical preparation, psychological preparation, financial preparation, cultural preparation, home preparation, and delivery preparation.